Land Surface Temperature Estimation Using Landsat 9 Satellite Imagery in Lamongan Regency, Indonesia - Noraini, Alifah; Sudiasa , I Nyoman (Poltanesa, 2024)
Gerbangkertasusila area (Gresik, Bangkalan, Mojokerto, Surabaya, Sidoarjo, and Lamongan) is a target area for accelerating economic development. Land use change are one of the phenomena that often occur in districts that have the potential for developing the area, one of the areas that has the potential to become a Creative Economy Zone is Lamongan Regency. This study aims to estimate changes in Land Surface Temperature (LST) in Lamongan Regency by utilizing Landsat 9 satellite imagery. Landsat 9 satellite imagery is processed based on a temperature algorithm for estimating temperature calculations. The Landsat 9 satellite was launched in 2021 and is a replacement satellite for the Landsat 8 satellite. The Landsat 9 satellite has 9 (nine) spectral bands and 2 (two) thermal bands. Estimation of LST uses band 4, band 5, and band 10. The LST algorithm used is the mono window algorithm. The mosaic process was carried out on path 118 raw 65 and path 119 raw 65. The results showed that the Lamongan Regency area has a greenish level with a value range of (-0.611) to 0.5 which is dominated by medium density levels. The estimation results of LST in Lamongan Regency are dominated by temperatures in the range of 23°C – 26°C with the highest temperature being 29°C – 33°C.